Soft-Tissue Laser in Dental Hygiene - Blayden, Jessica; Mott, Angie (: Wiley-Blackwell, 2013)
The uses benefits of soft-tissue lasers in dental hygiene practice are myriad. Lasers are used for more effective debridement, scaling and planning, with less pain and bleeding. Hygienists can detect sub- and supra-gingival calculus, remove the bacteria in pockets, and remove granulation, among other treatments. Soft-tissue Lasers in Dental Hygiene is the first book to explain laser use in periodontal therapy. Authors Jessica Blayden and Angie Mott are registered dental hygienists who have been using laser therapy in their dental hygiene practices for several years, and here they share their experience. Blayden and Mott begin by discussing laser history, physics, components, and safety. They then describe the specifics of periodontal therapy—what lasers can be used for, how to implement them, techniques, and protocols. The authors also present case studies that demonstrate how treatment plans are implemented for varying levels of periodontal disease. The authors conclude with chapters on patient communication and practice management.
Acknowledgments -- 1 Laser history 3 -- 2 Laser physics 9 -- 3 Laser components 19 -- 4 Lasers available in dentistry 27 -- 5 Periodontal therapy 47 -- 6 What can be achieved with lasers: possible guided-tissue regeneration 61 -- 7 Laser applications for the dental hygienist 75 -- 8 How to implement lasers in dental hygiene 79 -- 9 Communication skills for the dental hygienist 97 -- 10 Insurance codes: how is laser paid for? 107 -- 11 Laser cases 115 -- Appendix: further educational options for laser dental hygienists 219 -- Index 223
Keywords: LÁSER-ODONTOLOGÍA